CHARACTERISTICS OF GOLDEN APPLE SNAIL BIOSTIMULANTS AND AGRONOMIC EFFECTIVENESS TESTS ON THE COFFEE SEEDLINGS - Sepdian Luri Asmono; Rahmawati; Nisa Budi Arifiana; Dyah Nuning Erawati; Nurul Sjamsijah; N. Bambang Eko Sulistyono (BIOTROPIA, 2026)
ARTICLE HIGLIGHTS- Golden apple snail extract was successfully developed into a biostimulant containing NPK nutrients, 12 amino acids, and indole-3-acetic acid (IAA).- The biostimulant significantly enhanced coffee seedling growth, including plant height, root length, leaf area, chlorophyll content, and biomass.- Golden apple snail biostimulant achieved the highest Relative Agronomic Effectiveness (RAE) of 104%, outperforming conventional NPK fertilization.- Formulation without EM4 retained higher concentrations of macronutrients and amino acids, whereas EM4 supplementation increased IAA production.- Utilizing an invasive golden apple snail as a plant biostimulant provides a sustainable alternative to inorganic fertilizers for coffee nurseries. ABSTRACTThe use of Golden Apple Snail (GAS), an invasive species, as a potential biostimulant source represents an innovation, particularly in sustainable agriculture and waste management. Therefore, this study aimed to determine the biochemical characteristics of GAS and assess its effectiveness on coffee seedling growth. The first test, detecting biochemical characteristics, was conducted using two formulations, i.e., 1) Formulation 1 = 1,000 g of fresh whole GAS extract + 500 g of sugar and 2) Formulation 2 = 750 g of fresh whole GAS extract + 500 g of sugar + 125 mL of EM 4. The results of the 14-day fermentation showed the presence of nutrients N, P, K, 12 amino acids, and phytohormones. Formulation 1 had a total amount of N-Total (1.76%), P2O5 (0.18%) and K2O (0.29%) and a higher amino acid content than those in Formulation 2. In phytohormone detection, IAA was present in both formulations. The results of this test were used for further tests on the growth of Robusta coffee seedlings. The second test of agronomic effectiveness was carried out using a Randomized Block Design, with 6 types of fertilization treatments: 1) Control (Without GAS and NPK Biostimulants); 2) GAS Biostimulant 50 mL/L; 3) GAS Biostimulant 50 mL/L + ½ dose of NPK; 4) 0.5 g Urea + 1 g TSP + 1 g KCL; 5) GAS Biostimulant 50 mL/L + Full NPK Dose; 6) 1 g Urea + 2 g TSP + 2 g KCL. Each treatment was divided into 3 groups having two plants in each group. Observation data at the age of 4 months were tested using ANOVA and showed that there were significant differences in all morphological observation variables, including plant height, root length, number of leaves, chlorophyll content, leaf area, fresh weight, and dry weight or biomass. Based on the dry weight data, a Relative Agronomic Effectiveness (RAE) test was also conducted, which showed that the GAS Biostimulant treatment produced the highest RAE value, namely 104%, compared to the use of NPK fertilizer, showing agronomic effectiveness of GAS Biostimulant as an alternative to inorganic fertilizers in coffee nurseries.